HUBUNGAN PENGETAHUAN DENGAN SIKAP BIDAN TENTANG PARTOGRAF OLEH BIDAN PRAKTEK MANDIRI DI KECAMATAN BENGKONG KOTA BATAM TAHUN 2017 - Octarini, Tuti; Sihombing, Sarmauli Franshisca (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The World Health Organization recommends the use of partograph in the delivery room, 15% of complications in labor are not detected early due to the negligence of partograph filling. The purpose of this research is to know the correlation between the knowledge and attitude of a Midwife toward Partograf By Independent Midwifery Practice In Bengkong Regency, Batam Year 2017. This research is Analytical Observational with cross-sectional approach and using questioner as the primary data. Data sampling used is total sampling method. The study was conducted in June 2017, a sample size of 38 people. Data analysis using Chi-Square technique. The results showed that midwives, who were well-informed and had positive attitudes are numbered to 28 people (96.6%), those who had negative attitude are numbered only 1 (3.4%).Meanwhile, less knowledgeable midwives who had positive attitudes are 2 people (22.3 %) and negative attitude are 7 people (77,7%).There is a correlation between midwife knowledge with attitude toward partograph with p-value = 0.000. It Independent midwives are expected to improve the quality of their service and implement the use of partograph.Â